Mechanical and cracking behavior of porous rock models containing random circular defects under uniaxial compression - Ma, Wenqiang; Cui, Can; Li, Xiaoxiao (Frontiers in Physics, 2022)
Circular defects are widely distributed in porous rock materials, and the defects greatly affect the mechanical behavior and crack evolution of rock masses. In this paper, numerical models containing random circular defects are constructed based on discrete element method. Then, the uniaxial compressions are numerically performed to reveal the influence of the porosity or size homogeneity of the defects on the mechanical behavior, crack evolution, and acoustic emission (AE) events of the models. The results suggest that a univariant increase in porosity leads to a nonlinear decrease in the peak strength and a linear decrease in the elastic modulus. The number of cracks and AE events decrease with increasing porosity. As the size homogeneity coefficient increases, the peak strengths show a slight linear rise, while the elastic modulus values show a minimal linear downward trend, and the number of cracks and AE events show wave-like increases. The cracks first appear at the location with dense defects, and the cracks initiate from the top and bottom of the circular holes. The crack propagation and intersection modes between two adjacent defects are affected by their positions. These findings provide a reference for the fracture mechanism of rock with random circular defects.